Immunotherapy and Prevention of Cancer by Nanovaccines Loaded with Whole‐Cell Components of Tumor Tissues or Cells (Adv. Mater. 43/2021). Issue 43 (25th October 2021) - Ma, Lin; Diao, Lu; Peng, Zuofu; Jia, Yun; Xie, Huimin; Li, Baisong; Ma, Jianting; Zhang, Meng; Cheng, Lifang; Ding, Dawei; Zhang, Xuenong; Chen, Huabing; et al.
Abstract : Cancer Nanovaccines In article number 2104849, Mi Liu and co‐workers demonstrate a simple and universal method to prepare therapeutic and preventive cancer nanovaccines based on tumor tissues/cells. Such nanovaccines show both potent preventive and potent therapeutic efficacy in lung cancer, melanoma, and breast cancer. This universal method can be applied to make tumor‐cell‐based nanovaccines for cancer immunotherapy and prevention.